Fahr Hastalığı: İki Olgunun Bilgisayarlı Tomografi Bulguları - Savranlar, Ahmet; Bozgeyik, Zülkif; Kocakoç, Ercan; Kırış, Adem; Tabey, Faruk (Fırat University, 2002)
Fahr hastalığı, bilateral ve hemen daima simetrik olarak bazal ganglionlarda, subkortikal nükleuslarda ve beyaz cevherde kalsiyum ve diğer minerallerin depolandığı nadir bir hastalıktır. Klinik görünüm değişken olup nöbetler, rijidite ve demansla birlikte olabileceği gibi hiç bir nörolojik anormalliğin olmadığı olgular da olabilir. Fahr hastalığının tanısında yararlı bir görüntüleme tekniği olarak Bilgisayarlı Tomografi kullanılabilir. Biz, hastalıkla ilişkili bulgusu olmayan ve aşırı kalsifikasyonlara bağlı kognitif fonksiyon bozukluğu olan iki Fahr hastalıklı olgu sunuyoruz.

Fahr's disease is a rare disorder where bilateral, almost symmetric, calcium and other mineral deposits occur in basal ganglia, subcortical nuclei and white matter. The clinical pattern is variable and may be associated with seizures, rigidity, and dementia. Also cases with Fahr's disease may present without neurological abnormalities. Computed tomography may be used to for the diagnosis of Fahr's disease as an useful imaging technique. We present two cases with Fahr's disease. One of them had no symptoms related to disease and the other patient had a cognitive function disorders due to extensive calcifications.
Fahr's Disease: Computed Tomography Findings of Two Cases